Synthesis of the Kinase Inhibitors Nintedanib, Hesperadin, and Their Analogues Using the Eschenmoser Coupling Reaction - Marek, Lukáš; Váňa, Jiří; Svoboda, Jan; Hanusek, Jiří (American Chemical Society, 2021)
A novel synthetic approach involving an Eschenmoser coupling reaction of substituted 3-bromooxindoles (H, 6-Cl, 6-COOMe, 5-NO2) with two substituted thiobenzanilides in dimethylformamide or acetonitrile was used for the synthesis of eight kinase inhibitors including Nintedanib and Hesperadin in yields exceeding 76%. Starting compounds for the synthesis are also easily available in good yields. 3-Bromooxindoles were prepared either from corresponding isatins using a three-step synthesis in an average overall yield of 65% or by direct bromination of oxindoles (yield of 65-86%). Starting N-(4-piperidin-1-ylmethyl-phenyl)-thiobenzamide was prepared by thionation of the corresponding benzanilide in an 86% yield and N-methyl-N-(4-thiobenzoylaminophenyl)-2-(4- methylpiperazin-1-yl)acetamide was prepared by thioacylation of the corresponding aniline with methyl dithiobenzoate in an 86% yield.
Syntéza inhibitorů kinázy Nintedanibu, Hesperadinu a jejich analog s využitím Eschmoserovy reakce
Keywords: Eschenmoser reaction; 3-bromooxindoles; Nintedanib; Hesperadin; Eschenmoserova reakce; 3-bromoxindoly; Nintedanib; Hesperadin